G157(P) Antibody responses to immunizations in children with type i diabetes mellitus: A case-control study. (24th May 2017) - Eisenhut, M; Chesover, A; Misquith, R; Nathwani, N; Walters, A
Abstract : Background: Type I diabetes mellitus (DM) has been associated with abnormalities of T cells. Our objective was to assess whether antibody responses to T-cell-dependent and -independent antigens in children with DM are lower than those of children without DM. Methods: We performed a case-control study matching children with DM to children without DM by age and by assessing antibody levels to pneumococcal serotypes, Haemophilus influenzae, and tetanus and diphtheria toxoids and reassessing antibody levels in patients with antibody levels below protective thresholds after booster immunisation. Results: We recruited 36 children with DM and 36 age-matched controls. The mean age was 10 years. There was no difference between groups in antibody levels against the antigens tested. Pneumococcal antibody levels below the protective threshold were found in 35.9% of DM patients after conjugate pneumococcal vaccination with no difference between groups. Booster immunisation with unconjugated pneumococcal vaccine resulted in a median level against pneumococcal serotypes of 2.3 mg/ml (range, 0.05 to 664.7 mg/ml) in children with DM and 6.1 mg/ml (0.12 to 203.36 mg/ml) in children without DM (p=0.013). Over 85% of children had levels above the protective threshold after booster immunisation with no difference between groups. Conclusions: There was no evidence for a reduced antibody response to T-cell-dependent antigens given during childhood immunizations in children with DM. There was a reduced antibody response to antigens of pneumococcal strains in children with DM given unconjugated pneumococcal polysaccharide vaccine compared with that of children without DM without being associated with a difference in percentage of antibody levels below the protective threshold between groups.